ANALISIS PROTOTIPE PEMBANGKIT LISTRIK TENAGA BAYU (PLTB) TIPE SIRIP BALING-BALING DINAMIS POROS VERTIKAL - Suyanta Suyanta; Zahratul Jannah; Muh. Nasir Hariyanto (Universitas Tribhuwana Tunggadewi Malang, 2016)
Serves as a vertical windmill power generation derived from wind speeds that occur in areas that have a function of wind speed as power plants. so as to move / rotate to the next windmill can rotate the dynamo that can generate electrical energy. In this study, researchers wanted to develop a system by adding a dynamic fin, where fin is equipped with hinges that functioned as a reduction of pressure on the side of the lai. For more details can be followed in the design of a complete explanation on the basic theory pembahasa. At the end of this study can determine deferent between the fin and the fins remain dynamic in the manufacture of prototype vertical windmill. So in the end it can be seen which system is better , whether fixed or fins fin system dynamic , hoped this research can provide better advice to design a vertical axis windmill better.